Mary - Boss, Sarah Jane (New century theology., 2004)
In recent years Mary has stepped out of the closet of piety and devotion and become the subject of serious theological study and work. For too long Mary was an icon for the repression of women by a male dominated Church, but now Mary is seen as a vital theological symbol, a symbol of true femininity and true humanity which the Church and the modern world needs urgently. Jung has argued that the Definition of the Doctrine of the Assumption was the most important religious event since the Reformation: the feminine principle has been absorbed into the Godhead. Yet amongst some modern Catholics, a.